DYNAMICS OF TRADITIONAL MARKETS: ADAPTATION AND INNOVATION OF TRADERS IN INCREASING COMPETITIVENESS IN THE MARKET IKAN LAMA MEDAN - Hattaradzani, Shafiki; Muin, Mohd. Iqbal Abdul (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2024)
The Market Ikan Lama Medan, founded in 1890 by Tjong A Fie, this tax has undergone significant changes, initially specifically as a fish trading place, now developing into a trading center for textiles and other similar goods. This research focuses on the phenomenon being experienced by traders in traditional markets where they face difficulties in adapting to digital technology, and adapting their way of trading to the policies that arise as a result of these developments. This exploration requires a qualitative phenomenological approach to understand the adaptation and innovation of traders in traditional markets. The results show that traditional traders focus on product ordering efficiency and convenient service for customers. They also build good relationships with customers to increase sales, offering discounts and special services. Traders also improvise with modern technology, but still rely on direct interaction with customers through bargaining to set appropriate prices.Keywords: Traditional markets, trader innovation, technology adaptation, customer service